ANALISIS KOMPARATIF PREDIKSI KEBANGKRUTAN DENGAN MODEL ALTMAN Z-SCORE DAN MODEL SPRINGATE PADAPERUSAHAAN TAMBANG BATU BARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Try Justary Harvandy; Zirman Zirman; Rusli Rusli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to predict of bankruptcy by Altman Z—Score and Springate model Comparative analysis. Each company would have had a bankruptcy if it is not anticipated, therefore this study explains how the prevention or early steps to detect and predict bankruptcy. This study purpose to determine the bankrupcty prediction model is most suitable for use in its application to coal mining companies in Indonesia, by comparing two financial distress prediction model, the model of Altmant Z-Score and Springate. Comparisons were made by analyzing the accuracy of each model. The data used in the form of annual financial statements published by the company on the Indonesian Stock Exchange website. The sample used is a coal mining company in Indonesia listed on the Stock Exchange during the years 2010-2014. The sampling technique is purposive sampling with a total sample obtained by 7 companies. The results showed only 1 of 3 hypothesys was accepted. First, the result showed that there was no difference between Altman Z-Score model and Springate model was make accurate than Springate model by 71,43% accuracy level. So, the second hypothesys was rejected and third hypothesys was accepted.Keywords : Bankruptcy, Predictions Models, and Financial Ratio